Informacja i propaganda. Wczesne angielskie publikacje prasowe a Pierwsze Imperium Brytyjskie - Kalinowska, Anna (Imperium Brytyjskie: Rozważania interdyscyplinarne, 2019)
The text aims to present the earliest English newspapers’ efforts to inform about and comment upon the events related to England’s imperial ambition in the first half of the 17th century. Due to time concurrence between the beginnings of the English press and the emergence of the First British Empire, it is obvious that the two were interrelated. Newsbooks could have served as means of dissemination of news about new colonial initiatives, while people involved in colonial ventures were providing editors with topics to write about. However, the crucial moment when the press focused not only on informing, but also on propagating and promoting government’s imperial ambitions was mid-1650s’, especially the period of the English fleet’s expedition to the West Indies, known as The Western Design. As the plan to capture Hispaniola from Spain and turn it into an English stronghold in the Carribean had collapsed the press got involved into a “damage control” campaign coordinated by the government. The analysis of the news items published in one of the most popular titles, “Weekly Intelligencer”, proves that this campaign was quite successful, as even independent editors were eager to cooperate. Therefore, there are no arguments supporting the theory that their criticism could have been the reason for suppression of the press market in the late September 1655.